Objective methods for the assessment of passenger car steering quality - Harnett, Philip (Cranfield University, 2002)
Steering feel and quality are terms commonly used in the automotive industry when describing passenger car steering systems. However, a procedure for the quantification of these terms does not exist, let alone a concise definition of what they constitute. This thesis puts forward a hypothesis by which steering quality and feel are described by the input/output relationships of the steering system and how they are perceived by the driver. Good control properties are postulated for these relationships and an experiment is conducted, where they are altered in a manner proposed to affect quality. A methodology for the objective assessment of the control properties is developed, employing vehicle dynamic testing and representation by a mathematical model. This is put into practice to evaluate the outcome of the experiment. It was found that the methodology was successful in detecting and quantifying the alteration in the vehicle control properties. A subjective evaluation was performed to assess the experiment in terms of the quality and feel perceived by the driver. The subjective judgement delivered a result, where the deviation in quality agreed with the objective quantities hypothesised to describe quality. The thesis provides a significant step in the understanding of what is termed steering feel and quality. The methodology, successful in quantifying the experimental results with respect to quality, constitutes a scientific advancement in the current procedures for the assessment of steering quality.